191k views
4 votes
Solve -3(2x-3)+10x=3q

User Jaka
by
5.1k points

2 Answers

6 votes

Answer:

4x+9=3q

Explanation:

-3(2x-3)+10x=3q

-6x+9+10x=3q

4x+9=3q

User The Cookies Dog
by
5.3k points
0 votes

Answer:

q = 4/3x + 3

Explanation:

-3(2x-3)+10x=3q

Multiply the -3 at the beginning by (2x - 3), the parenthesis

-6x + 9 + 10x = 3q

Now combine the like terms (add x's and variables separately)

(-6x + 10x) + 9 = 3q

4x + 9 = 3q

Divide both sides of the equation by 3

(4x + 9) รท 3 = q

4x/3 + 9/3 = q

Simplify

q = 4/3x + 3

Hope this helps :)

User Bluenile
by
4.4k points